PENERAPAN METODE RIA DALAM PEMBENTUKAN PERJANJIAN INTERNASIONAL: UPAYA OPTIMALISASI KETERLIBATAN RAKYAT DALAM MEWUJUDKAN NEGARA KESEJAHTERAAN - Hamdani, Fathul; Fauzia, Ana; Putra, Eduard Awang Maha (Jurnal Yuridis, 2023)
From the Welfare State perspective, the state is also referred to as a social services state or an agency of services. The form of social services from the state in the context of realizing general welfare is that the government in building international cooperation must always consider national interests through community participation. This study aims to evaluate the practice of forming international agreements concerning people's participation, and analyzing how the RIA method can increase people's involvement in the formation of international agreements. Writing this article applies normative legal research methods, with statutory, conceptual, and comparative approaches. The research results show that the involvement of the House of Representatives as a form of people's participation in the formation of international agreements can be said to be quite minimal. In contrast to some countries such as Germany, the House of Representatives or parliament must be provided with information regarding the negotiation process that is being carried out by the Government. Likewise in the United States, Parliament can participate in the negotiation process on international agreements for certain fields. Even though Article 2 of the Law on International Agreements mentions a mechanism for consultation by the government regarding international agreements that concern the public interest. However, there is no further explanation of whether the Consultation mechanism is voluntary or an obligation for the executive. Therefore, one of the methods that can be applied to increase public participation, especially through the involvement of the House of Representatives is to apply the RIA method.